2021
DOI: 10.1200/go.20.00663
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Oncology Clinical Research in Latin America (LACOG 0420)

Abstract: PURPOSE COVID-19 has affected cancer care worldwide. Clinical trials are an important alternative for the treatment of oncologic patients, especially in Latin America, where trials can be the only opportunity for some of them to access novel and, sometimes, standard treatments. METHODS This was a cross-sectional study, in which a 22-question survey regarding the impact of the COVID-19 pandemic on oncology clinical trials was sent to 350 representatives of research programs in selected Latin American institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 35 publications
7
13
0
2
Order By: Relevance
“…It is important to compare the “Portuguese reality” during the worst COVID-19 wave with that of other countries under similar circumstances. To this end, results of the current study are in line with those reported in studies in other countries [ 36 , 37 ]. For example, a similar study utilizing a 29-question survey with responses from 165 medical oncologists accessed via the Italian Association of Medical Oncology (AIOM) and Italian Breast Cancer Study Group (GIM) mailing lists, showed reduced use of (neo)adjuvant weekly paclitaxel or a dose-dense schedule for anthracycline-based chemotherapy during the COVID-19 outbreak, and reduced use of first-line weekly paclitaxel for HER2-positive disease or CDK4/6 inhibitors for luminal tumors with less aggressive characteristics in the metastatic setting [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is important to compare the “Portuguese reality” during the worst COVID-19 wave with that of other countries under similar circumstances. To this end, results of the current study are in line with those reported in studies in other countries [ 36 , 37 ]. For example, a similar study utilizing a 29-question survey with responses from 165 medical oncologists accessed via the Italian Association of Medical Oncology (AIOM) and Italian Breast Cancer Study Group (GIM) mailing lists, showed reduced use of (neo)adjuvant weekly paclitaxel or a dose-dense schedule for anthracycline-based chemotherapy during the COVID-19 outbreak, and reduced use of first-line weekly paclitaxel for HER2-positive disease or CDK4/6 inhibitors for luminal tumors with less aggressive characteristics in the metastatic setting [ 36 , 37 ].…”
Section: Discussionsupporting
confidence: 92%
“…For example, a similar study utilizing a 29-question survey with responses from 165 medical oncologists accessed via the Italian Association of Medical Oncology (AIOM) and Italian Breast Cancer Study Group (GIM) mailing lists, showed reduced use of (neo)adjuvant weekly paclitaxel or a dose-dense schedule for anthracycline-based chemotherapy during the COVID-19 outbreak, and reduced use of first-line weekly paclitaxel for HER2-positive disease or CDK4/6 inhibitors for luminal tumors with less aggressive characteristics in the metastatic setting [ 36 , 37 ]. Furthermore, a cross-sectional study (LACOG 0420) surveying investigators and research coordinators ( n = 90) from research centers in Latin America demonstrated that oncology clinical trials have been significantly affected during the pandemic in Latin America [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical COVID-19 studies were found in all LAC countries but were mainly concentrated in six countries that accounted for almost three quarters of all the included papers (Brazil, Mexico, Colombia, Peru, Chile and Argentina), while Uruguay, Panama, Trinidad and Tobago, Chile and Costa Rica had the highest rate of publications per population, with Haiti and Venezuela having the lowest. This coincides with other studies finding a similar list of countries at the top and bottom of research production among LAC countries, for instance during the COVID-19 pandemic with oncology clinical trials [19] and before the pandemic with pharmacological RCTs [20] and clinical trials [21]. The latter also found that over 80% of trials were concentrated in three countries (Brazil, Mexico and Argentina), while the present review found a larger participation of other LAC countries as well, showing that the pandemic probably has pushed for a more country widespread research generation.…”
Section: Plos Onesupporting
confidence: 92%
“…Existing disparities in equitable access to timely and effective cancer care globally are expected to increase as the gap widens between healthcare systems with and without sufficient resources to mitigate the negative effects of the pandemic on cancer prevention, early diagnosis and treatment -as well as access to COVID-19 vaccines [2]. Furthermore, the pandemic has exposed significant deficits in how cancer care and health systems prepare, respond and mitigate such events [3,4].…”
Section: Introductionmentioning
confidence: 99%